Impact of Human Resources Innovation on the Evolution of the Tourism Sector in Bali Indonesia Post-Covid-19 Pandemic - Putu Herny Susanti; I Made Darsana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The impact that was felt by the COVID-19 pandemic was that many workers were laid off and the economy of the community experienced a very deep decline. Not only workers in the tourism sector but in various other sectors also feel the impact. The tourism gap period is indeed very influential for the development of tourism in Bali and in Indonesia. The pause period can be used as a reference for self-evaluation. Tourism thinking related to tourism activities has become more organized and neater. The innovations made by the Central Government and the Regional Government of West Nusa Tenggara (NTB) are very worthy to be imitated for the rise of Bali tourism. The impact of the COVID-19 pandemic for almost 3 years has greatly destroyed Bali's tourism, and has had an impact on Bali's economic downturn.